Studies Separation of Gas Mixtures by Membrane - Ahmad, Farooq (2008)
Gas separation using membrane process is getting more attention since the last decade. This is due to the advantages offered by the membrane process, such as, compactness, simplicity and energy savings. The present work focuses on the study of permeability and selectivity characteristics of both porous and non-porous membranes for separation of carbon dioxide and other gases from natural gas. Pore flow model with capillary condensation mechanism have been used to explore the separation of carbon dioxide, hydrogen sulfide, propane, butane and nitrogen from its binary mixture with methane by a nano-porous membrane. The carbon dioxide from C02/CH4 binary mixture, hydrogen sulfide from H2 S/C~ binary mixture, propane from C3Hs/CH4 and butane from C4H10/CH4 binary mixture was found to preferentially permeate through the membrane pores thus blocking the flow of methane. The methane left on the permeate side was found to be slightly soluble in the condensed phase. In case of N2/C~ binary mixture, methane was found to be preferentially permeated through the membrane pores. The nitrogen left was found to be slightly soluble in the condensed methane. The Kelvin equation has been used to analyze the condensation phenomena.The highest permeability of 1150 gmol/ m2.s.bar for condensed carbon dioxide in C02/CH4 binary mixture was found followed by 800 gmol/m2.s.bar for condensd methane in N2/C~. 700 gmol/m2.s.bar for condensed hydrogen sulfide in H2S/C~ binary mixtures respectively. In case of C3 and C4 highest permeability of 700 gmol/m2 s.bar were achieved for propane in C3H8/CH4 binary mixture, followed by 500 gmol/m2 .s.bar for butane in C4H10/CH4 binary mixture, respectively.The data obtained from the computed results were compared reasonably well with the published experimental data. The separation factor of N2/CH4 was found to be the highest with 439 followed by the separation ofH2S/CH4 and C02~~, respectively. In case oflower hydrocarbons, C3 and C4, a highest selectivity of 140 was achieved in C4H10/CH4 binary mixture followed by 75 in C3H8/CH4 binary mixture, respectively.Experimental work was conducted to study the permeability and selectivity of pure carbon dioxide, methane and its binary mixture at various feed pressure, temperature and composition through non-porous silicone rubber membranes. The permeability of pure methane and carbon dioxide was found to increase with pressure, where as such plots for carbon dioxide become convex towards pressure axis at higher pressure (17 bars) due to reduction in free volume of the polymer. The experimental results showed that for binary mixture of carbon dioxide and methane, permeability was found to be not only dependent on the feed gas pressure but also dependent on the molar composition of feed gas. The permeation flux was found to increase with pressure difference, and the enhancement of the proportion of the carbon dioxide in the feed gas. Experimental results showed that the selectivities estimated from pure gas varied slightly with an increase in the feed pressure but reached to a maximum value of 11.4. With 20 % C02 in the feed stream, the selectivity was found to be lower by a factor of two to three times than that of pure components over the whole pressure range. High selectivities were obtained at 80% C02 in the feed stream. An analytical model expressed in terms of pressure and feed composition was derived from permeability behavior of pure carbon dioxide and methane to predict quantitatively the permeability of binary mixtures. It was indicated that the model could be used to evaluate the separation properties and to choose the optimal feed compositions for the membrane separation systems of carbon dioxide and methane.